"Helhedens Forstaaelse". Peter Hansens Litteraturhistorie - Gissel, Jon A.P. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2016)
Peter Hansen (Copenhagen 1840 – Hellerup 1905) was a journalist and essayist, who wrote energetically and in a lively manner, and who was also active as a translator. His Illustrated History of Danish Literature in three volumes is important, especially the third volume, which makes it possible to approach Danish literature of the 19th century in many ways. This comprehensive volume is an important instrument of research with regard to those parts of the literature of this period, which have not received much attention from posterity, such as the writers on the Conservative side of the cultural debate in the last third of the century. The article investigates in which sense this history of literature can be termed conservative, describes its views and interests, including how it refers to Christianity, patriotic feeling, and the conservative writers. Hansen’s work puts emphasis on a national revival and less on a religious one. The unified whole is presented as a philosophy of life, and History means exceedingly much within this totality. Peter Hansen wished to see Danish culture as a unity, making scholarship also a part of the literature, and he made various scholars write descriptions of their own disciplines in the 19th century. P. Hansen puts emphasis on clarity, in the authors he is dealing with, as well as in his own presentation. He also wants to avoid exaggerations, e.g. with regard to national feelings, which are otherwise a mayor concern to him. The main impression is therefore a broad and balanced representation of the topic, mainly in accordance with the National Liberal movement of the century. The article shows that this attitude manifests itself also in a lack of criticism as to principles of the cultural radicalism of the day, despite expressing opposition to certain means of fighting in the debate. An attitude to life is rather reflected in the optimism which he maintains contrary to the pessimism of the naturalists.